2008
DOI: 10.1111/j.1365-2788.2007.01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Social goals and conflict strategies of individuals with mild to moderate intellectual disabilities who present problems of aggression

Abstract: While the findings of this study are tentative, investigating the social outcomes that are valued by individuals with ID who present problems of aggression appears to be a promising area for further research, with possible implications for clinical assessment and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…It was found that aggressive and nonaggressive groups generated the same number of assertive and passive responses, suggesting that the aggressive actions of the aggressive group were not due to an inability to generate alternatives. Pert and Jahoda (2008) did not find evidence to support the view that the aggressive participants were less able than the nonaggressive group to generate a range of behavioral responses in line with the social goals they were asked to achieve. Pert and Jahoda (2008) used a different method, and asked participants to generate responses to meet five predefined goals of (1) peer approval, (2) authority approval, (3) instrumental reward, (4) effect on victim and (5) self condemnation.…”
Section: Response Generation and Evaluationmentioning
confidence: 66%
See 3 more Smart Citations
“…It was found that aggressive and nonaggressive groups generated the same number of assertive and passive responses, suggesting that the aggressive actions of the aggressive group were not due to an inability to generate alternatives. Pert and Jahoda (2008) did not find evidence to support the view that the aggressive participants were less able than the nonaggressive group to generate a range of behavioral responses in line with the social goals they were asked to achieve. Pert and Jahoda (2008) used a different method, and asked participants to generate responses to meet five predefined goals of (1) peer approval, (2) authority approval, (3) instrumental reward, (4) effect on victim and (5) self condemnation.…”
Section: Response Generation and Evaluationmentioning
confidence: 66%
“…The participants were asked to comment on whether the outcomes would meet the same predefined goals of (1) peer approval, (2) authority approval, (3) instrumental reward, (4) effect on victim and (5) self condemnation. Kirk et al (2008) found that aggressive participants anticipated more positive outcomes from aggressive behavior than nonaggressive people, whereas Pert and Jahoda (2008) found no differences for views of aggression. Pert and Jahoda (2008) pointed out that while it is often assumed that the awareness of " negative" outcomes will act as a deterrent, the impact of outcome will vary from person to person depending on cultural norms, normative beliefs, past experiences and self-concept.…”
Section: Response Generation and Evaluationmentioning
confidence: 92%
See 2 more Smart Citations
“…In this case, Pert & Jahoda () found that the ‘social goals’ of individuals with and without difficulties with aggression differed. Namely, the majority of ‘non‐aggressive’ participants' responses suggested that they were seeking a ‘fair solution’ when presented with a hypothetical situation in which another person was hostile to them, whilst those with difficulties of aggression sought to ‘show power’ to the other party.…”
Section: Resultsmentioning
confidence: 96%